Blood eosinophils: a biomarker of COPD exacerbation reduction with inhaled corticosteroids - Siddiqui, S; Pavord, I; Barnes, N; Guasconi, A; Lettis, S; Pascoe, S; Petruzzelli, S (Dove Press, 2018)
Background Growing evidence suggests that blood eosinophil count is associated with patient responsiveness to inhaled corticosteroids (ICS). We performed post hoc predictive modeling on data from the FORWARD study and two replicate studies by Dransfield, to evaluate the relationships between baseline eosinophil count and the effect of ICS on exacerbations and lung function in patients with COPD. Methods The studies assessed ICS/long-acting β2 agonist (LABA) combinations vs LABA alone. Using data from each study, we modeled COPD exacerbation rates, predose FEV1, and St George’s Respiratory Questionnaire score ([FORWARD only]) over a continuous range of eosinophils (0–1,000 eosinophils/μL in FORWARD, 0–993 eosinophils/μL in Dransfield). Results In all studies, ICS/LABA reduced exacerbations versus LABA alone across all eosinophil levels, with progressively greater reductions at increasing baseline blood eosinophil counts. In FORWARD, annual exacerbation rates ranged from 0.78 to 0.83 per year between 0 and 1,000 eosinophils/μL in the ICS/LABA arm, and from 0.81 to 1.54 per year in the LABA-only arm. In the Dransfield studies, exacerbation rates ranged from 0.54 to 1.02 per year in the ICS/LABA arm between 0 and 993 eosinophils/μL, and from 0.56 to 1.75 per year in the LABA-only arm. Change in FEV1 was not associated with eosinophil count in ICS-treated patients in FORWARD, whereas an increased treatment benefit in terms of FEV1 was observed at higher eosinophil levels in the Dransfield studies. ICS/LABA led to greater improvements in St George’s Respiratory Questionnaire total scores compared to LABA alone in patients in FORWARD with $67 eosinophils/μL. Conclusion Higher blood eosinophil count in patients with COPD is associated with an increased beneficial effect from ICS in terms of exacerbation reduction. Further prospective data are required to assess the role of blood eosinophils as a biomarker for therapeutic recommendations.